Historical Dictionary of German Intelligence - Adams, Jefferson, (Rowman & Littlefield Publishers, 2009)
No country can rival the sheer diversity of intelligence organizations that Germany has experienced over the past 300 years. Given its pivotal geographical and political position in Europe, Germany was a magnet for foreign intelligence operatives, especially during the Cold War. As a result of this, it is no wonder that during certain periods of history Germany was probably busier spying on its own citizens than on its enemies. Because of the Gestapo and the SS of Nazi Germany to the Stasi of the German Democratic Republic, the fear of domestic abuse by security agencies with police powers runs far deeper in German society than elsewhere in the West. The Historical Dictionary of German Intelligence presents the turbulent history of German intelligence through a chronology, a bibliography, and hundreds of cross-referenced dictionary entries on the agencies and agents, the operations and equipment, the tradecraft and jargon, and many of the countries involved. No military reference collection is complete without it.